The Implementation of a Successive Cancellation Polar Decoder on Xilinx System Generator - Arli, A.Ç.; Colak, A.; Gazi, O. (Institute of Electrical and Electronics Engineers Inc., 2017)
Polar coding is the first kind of the capacity achieving codes which are defined for binary-input discrete memoryless channels initially. Parallel processing property of the FPGA allows to decode faster with a margin of complexity. Xilinx System Generator as a practical tool to construct decoding designs in shorter time is a fact. In this study, FPGA implementation of decoding polar codes through Xilinx System Generator is shown. © 2023 Elsevier B.V., All rights reserved.
Keywords: Coding Theory; FPGA; Parallel Decoding; Paralel Decoding